Mapping of the internal environment and contour conditions of housing for broilers using computational fluid dynamics techniques - Souza, S. R.L. [UNESP]; Bueno, L. G.F.; Sabino, L. A.; Sousa, V. R.; Moura, D. J.; Carvalho, T. M.R. (My University, 2013)
The housing environment of broilers has a direct influence on production, because an unhealthy indoor environment affects poultry welfare. The objective of this study was to map the internal environment of the broiler house and detect the dispersion of gaseous pollutants through simulation, with the aim of achieving welfare and comfort for the poultry. For this, we used CFD (Computational Fluid Dynamics) techniques with which it was possible to estimate various situations for the same problem by changing parameters, verifying the results for different boundary conditions and analysing the risks with confidence and speed. Data were collected in two sheds at a commercial broiler farm located in Campinas, for broilers at 28, 35 and 42 days old. In both sheds G1 and G2, the conditions near the hoods were of higher intensity than other locations in the shed, with no homogeneity in the region of the litter. The simulator proved to be a good tool for determining the behaviour of NH3 and of the air circulating inside the sheds.
Keywords: Broilers; Monitoring and control of environmental and computational fluid dynamics